Penerapan Senam Sehat Gembira Pada Lansia di Desa Totoharjo Kecamatan Purbolinggo Kabupaten Lampung Timur - Oktaviana, Anita; S, Sefriyanti (Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this community service activity is to improve the active behavior of the community, especially in the health sector, so that it can improve healthy living behavior in the elderly and become a productive community in their daily activities. The community service program that has been implemented in Totoharjo Village aims to improve public health, especially the elderly. This happy healthy exercise activity is carried out on a scheduled basis every Tuesday afternoon and Friday afternoon, attended by the local community. This afternoon exercise activity is one of the concrete efforts of the community service team in providing a positive contribution to the Totoharjo Village community in increasing awareness of the importance of health and a healthy lifestyle.